2016
DOI: 10.1007/s11064-016-1914-0
|View full text |Cite
|
Sign up to set email alerts
|

Morin Mitigates Chronic Constriction Injury (CCI)-Induced Peripheral Neuropathy by Inhibiting Oxidative Stress Induced PARP Over-Activation and Neuroinflammation

Abstract: Neuropathic pain is initiated or caused due to the primary lesion or dysfunction in the nervous system and is proposed to be linked to a cascade of events including excitotoxicity, oxidative stress, neuroinflammation and apoptosis. Oxidative/nitrosative stress aggravates the neuroinflammation and neurodegeneration through poly (ADP) ribose polymerase (PARP) overactivation. Hence, the present study investigated the antioxidant and anti-inflammatory effects of the phytoconstituent; morin in chronic constriction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 71 publications
1
32
0
Order By: Relevance
“…) is sufficient to suppress neuro‐inflammation in bone cancer pain. A previous study showed that 30 mg/kg morin could attenuate the expression of pro‐inflammatory cytokines and relieve pain hypersensitivity in chronic constriction injury pain model (Komirishetty et al ., ). The present study extends to neuropathic pain model and demonstrates that morin shows therapeutic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…) is sufficient to suppress neuro‐inflammation in bone cancer pain. A previous study showed that 30 mg/kg morin could attenuate the expression of pro‐inflammatory cytokines and relieve pain hypersensitivity in chronic constriction injury pain model (Komirishetty et al ., ). The present study extends to neuropathic pain model and demonstrates that morin shows therapeutic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The response of the rat was noted for 20 seconds, and the response was graded on a 4‐point scale: 0, no response; 1, quick withdrawal or flicking the paw; 2, prolonged withdrawal or repeated flicking; and 3, repeated flicking of the paw with licking of the paw. With a time gap of 5 minutes, acetone was applied thrice onto the hind paw and the individual scores noted in 20‐seconds intervals were added to obtain a single cumulative score with a minimal score of 0 and a maximum score of 9 …”
Section: Methodsmentioning
confidence: 99%
“…Lee et al proved that morin administration ameliorated oxidative stress, inflammation, and mitochondrial dysfunction in a 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP)‐induced mice model of Parkinson's disease (PD) . Moreover through our previous studies, we have observed that morin exhibits potent anti oxidative and anti inflammatory effects against experimental chronic constriction injury (CCI)‐Induced peripheral neuropathy by reducing ROS . Being known for its role in ameliorating ROS generation, in this study we evaluated the neuroprotective properties of morin in STZ‐induced diabetic rats and high glucose‐induced metabolic stress in mouse neuroblastoma (N2A) cells.…”
Section: Introductionmentioning
confidence: 93%